The concept of the ‘right to be forgotten’, ‘right to delete’, ‘right to erasure’ in the digital age. - Sylvia, Papadopoulos (University of Pretoria, 2024)
Dissertation (LLM (Mercantile Law))--University of Pretoria, 2023.